2018
DOI: 10.17356/ieejsp.v4i3.396
|View full text |Cite
|
Sign up to set email alerts
|

Roma within Obstructing and Transformative Spaces

Abstract: The aim of our article is to inquire into the interconnectedness of local social context, mobility processes and social transformations. We argue that migratory patterns of the local Roma population in ethnically mixed communities are shaped by the degree and modes of maintenance of social distance between the Roma and local majority. While social distance can shape the ways migrant networks develop, it also influences the way remittances are invested at home. The analysis focuses on the comparison of two rura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The study of Roma disadvantages using qualitative methods has been the subject of several anthropological monographs (Engebrigtsen 2007;Fosztó 2009;Olivera 2012;Szeman 2017;Racleş 2021). There have also been studies using a complex methodology, combining the sociological survey method with anthropological fieldwork in an attempt to complement the survey data obtained with questionnaires with qualitative data and interpretations (Bădescu et al 2007;Fleck and Rughinis , 2008;Cace et al 2010;Toma et al 2017;Toma and Fosztó 2018). In an extensive research, Cace et al (2010) with combined methods studying urban and rural communities, showed that the employment situation of people in Roma communities can be characterized by low formal employment rates (a low share of those employed with a contract of employment; a lack of work history in the workbook), a high share of those employed in the informal economy or in subsistence agriculture, activities performed without qualification or on the basis of low qualification or non-formal (without supporting documents) based only on experience or tradition.…”
Section: Theoretical Context: the Situation Of The Roma In Romaniamentioning
confidence: 99%
See 1 more Smart Citation
“…The study of Roma disadvantages using qualitative methods has been the subject of several anthropological monographs (Engebrigtsen 2007;Fosztó 2009;Olivera 2012;Szeman 2017;Racleş 2021). There have also been studies using a complex methodology, combining the sociological survey method with anthropological fieldwork in an attempt to complement the survey data obtained with questionnaires with qualitative data and interpretations (Bădescu et al 2007;Fleck and Rughinis , 2008;Cace et al 2010;Toma et al 2017;Toma and Fosztó 2018). In an extensive research, Cace et al (2010) with combined methods studying urban and rural communities, showed that the employment situation of people in Roma communities can be characterized by low formal employment rates (a low share of those employed with a contract of employment; a lack of work history in the workbook), a high share of those employed in the informal economy or in subsistence agriculture, activities performed without qualification or on the basis of low qualification or non-formal (without supporting documents) based only on experience or tradition.…”
Section: Theoretical Context: the Situation Of The Roma In Romaniamentioning
confidence: 99%
“…In an extensive research, Cace et al (2010) with combined methods studying urban and rural communities, showed that the employment situation of people in Roma communities can be characterized by low formal employment rates (a low share of those employed with a contract of employment; a lack of work history in the workbook), a high share of those employed in the informal economy or in subsistence agriculture, activities performed without qualification or on the basis of low qualification or non-formal (without supporting documents) based only on experience or tradition. In the Migrom project (see Toma et al 2017Toma et al , 2018, they studied the international migration of Roma in Romania, including the effects of migration to home communities or return migration. This is very useful information that has the social context in which the Roma returned, forced by the lockdown of the COVID-19 pandemic, which we will analyze in this study.…”
Section: Theoretical Context: the Situation Of The Roma In Romaniamentioning
confidence: 99%
“…In the countries of origin, the remittances used to improve or construct new houses do not simply represent a symbolic affirmation of success. They also play a central role in remodelling ethnic landscapes through activating desegregation processes that challenge existing patterns of ethnic relations (Tesăr, 2015;Toma & Fosztó, 2018).…”
Section: Migration Residential Strategies and Homemaking Practicesmentioning
confidence: 99%
“…Notably, besides representing a symbolic affirmation of success, the 'remittance houses' (Lopez, 2010) of the Roma are part of broader, spontaneous processes of material and symbolic desegregation that challenge the existing patterns of ethnic relations in the villages and towns of origin (Toma & Fosztó, 2018). As Racles (2018) has highlighted, building or ameliorating a property house 'back home' also represents a response to anti-Gypsist repertoires that construct the 'Gypsy way of living' as bearing a natural predisposition to carelessness towards the inhabited space and the incapacity to overcome deprivation.…”
Section: Homemaking and Social Transformationsmentioning
confidence: 99%
“…The impact of migration on communities of origin around the world has been identified at several levels and dimensions of social life. Seasonal migration affects local and national economies and can transform the political landscape [6,57]. The labour market at origin is affected by seasonal migration [58].…”
Section: Community Levelmentioning
confidence: 99%